Multiple Reflections for Classical Particles Moving under the Influence of a Time-Dependent Potential Well - Graciano, Flávio Heleno [UNESP]; da Costa, Diogo Ricardo [UNESP]; Leonel, Edson D. [UNESP]; de Oliveira, Juliano A. [UNESP] (MDPI, 2022)
We study the dynamics of classical particles confined in a time-dependent potential well. The dynamics of each particle is described by a two-dimensional nonlinear discrete mapping for the variables energy (Formula presented.) and phase (Formula presented.) of the periodic moving well. We obtain the phase space and show that it contains periodic islands, chaotic sea, and invariant spanning curves. We find the elliptic and hyperbolic fixed points and discuss a numerical method to obtain them. We study the dispersion of the initial conditions after a single iteration. This study allows finding regions where multiple reflections occur. Multiple reflections happen when a particle does not have enough energy to exit the potential well and is trapped inside it, suffering several reflections until it has enough energy to exit. We also show deformations in regions with multiple reflection, but the area remains constant when we change the control parameter (Formula presented.). Finally, we show some structures that appear in the (Formula presented.) plane by using density plots.
Keywords: dispersion of the initial conditions; multiple reflections; time-dependent potential well